(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Heading is an important basic technique in soccer that requires abdominal muscle strength to produce an effective header. However, there is still little research that specifically examines the relationship between abdominal muscle strength on heading ability, especially in adolescent athletes. This study aims to determine the contribution of abdominal muscle strength (sit-ups with the ball) to heading ability in Persela Lamongan Academy soccer athletes aged 17 years. This study used a quantitative approach with an experimental design, while measuring abdominal muscle strength using a 30-second sit-up test, and heading ability was measured through a heading accuracy test. The study sample consisted of 16 Persela Lamongan Academy U-17 athletes. The results showed that the majority of athletes were in the 21–24 sit-up interval class, with a percentage of 93.7%. The best heading ability was also in the 15–18 interval class with a percentage of 87.5%. Data analysis showed the contribution of abdominal muscle strength to the heading ability of 91.3%. Abdominal muscle training significantly contributes to improving heading ability in adolescent soccer athletes.